1998
DOI: 10.1074/jbc.273.17.10190
|View full text |Cite
|
Sign up to set email alerts
|

Transport and Metabolism of the Essential Vitamin Pantothenic Acid in Human Erythrocytes Infected with the Malaria Parasite Plasmodium falciparum

Abstract: The growth of the human malaria parasite, Plasmodium falciparum, within its host erythrocyte is reliant on the uptake of a number of essential nutrients from the extracellular medium. One of these is pantothenic acid, a water-soluble vitamin that is a precursor of coenzyme A. In this study we show that normal uninfected erythrocytes are impermeable to pantothenate but that the vitamin is taken up rapidly into malaria-infected cells via a transport pathway that has the characteristics (furosemide sensitivity, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
235
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 214 publications
(243 citation statements)
references
References 24 publications
7
235
1
Order By: Relevance
“…In the only study on the subject, Annous and Song (9) reported that although pantothenate is phosphorylated within rat erythrocytes (the first step in CoA biosynthesis), there is no evidence for the subsequent steps of the CoA biosynthesis pathway. Saliba et al (10) confirmed that human erythrocytes similarly phosphorylate pantothenate, but did not investigate whether CoA synthesis also occurs in the cells. A lack of CoA biosynthesis in mammalian erythrocytes would seemingly place the burden of CoA synthesis squarely on malaria parasites that infect mammals (such as P. falciparum), contrary to the situation in birds.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In the only study on the subject, Annous and Song (9) reported that although pantothenate is phosphorylated within rat erythrocytes (the first step in CoA biosynthesis), there is no evidence for the subsequent steps of the CoA biosynthesis pathway. Saliba et al (10) confirmed that human erythrocytes similarly phosphorylate pantothenate, but did not investigate whether CoA synthesis also occurs in the cells. A lack of CoA biosynthesis in mammalian erythrocytes would seemingly place the burden of CoA synthesis squarely on malaria parasites that infect mammals (such as P. falciparum), contrary to the situation in birds.…”
mentioning
confidence: 69%
“…The cells were washed (four times) and suspended in pantothenate-free medium, pH 7.4. For experiments with parasites isolated from their host erythrocyte, following enrichment to Ͼ95% parasitemia, trophozoite stage P. falciparum-infected erythrocytes in suspension were treated with saponin (0.05% (w/v)) essentially as described previously (10). Following treatment with saponin, which permeabilizes the erythrocyte and parasitophorous vacuole membranes that enclose the parasite, while leaving the parasite plasma membrane intact, the cells were washed (four times) and suspended in pantothenate-free medium, adjusted to pH 7.1 to match the pH in the cytosol of a human erythrocyte infected with a trophozoite stage P. falciparum parasite (13).…”
Section: Methodsmentioning
confidence: 99%
“…the estimated intracellular concentration relative to the extracellular concentration), rather than amounts of nucleoside taken up, in order to facilitate the assessment of whether the radiolabel equilibrates between the intra-and extracellular solutions or is taken up to levels that exceed those that can be accounted for by equilibrative transport. The concentration of radiolabel inside the cells was calculated by dividing the amount of radiolabel associated with the cells by the intracellular water volume of the pellet, calculated from the cell count using the previously reported value of 28 fl for the cell water volume of parasites isolated by saponin permeabilization of the host cell (Saliba et al, 1998). Distribution ratios were calculated by dividing this intracellular concentration of radiolabel by the concentration of radiolabel in the extracellular solution.…”
Section: Transport Measurements In Isolated Parasitesmentioning
confidence: 99%
“…Parasites were 'isolated' from their host erythrocytes by treating parasitized erythrocytes with saponin as described elsewhere (Saliba et al, 1998). Saponin renders the erythrocyte and parasitophorous vacuole membranes permeable to macromolecules (Ansorge et al, 1996) but leaves the parasite plasma membrane intact and able to maintain transmembrane ion gradients (Saliba and Kirk, 1999;Alleva and Kirk, 2001) as well as a substantial membrane potential (Allen and Kirk, 2004).…”
Section: Parasite Preparationmentioning
confidence: 99%
See 1 more Smart Citation